Quantifying male harm and its divergence. (20th March 2022) - Colpitts, Julie; Jarvis, Will M. C.; Agrawal, Aneil F.; Rundle, Howard D.
Abstract: Male harm arises when traits that increase reproductive success in competition with other males also harm females as a side effect. The extent of harm depends on male and female phenotypes, both of which can diverge between populations. Within a population, harm is inferred when increased exposure to males reduces female fitness, but studies of the divergence of male harm rarely manipulate male exposure. Here, we quantify male harm and compare its magnitude between two lab populations of Drosophila serrata that were derived from a common ancestor 7 years earlier and subsequently held under conditions that minimized environmental differences. We manipulated female exposure to males in a factorial design involving all four combinations of males and females from these populations, providing insight into divergence in both sexes. Our results reveal substantial harm to females and provide stronger evidence of divergence in males than in females. Using these and other published data, we discuss conceptual issues surrounding the quantification and comparison of harm that arise because it involves a comparison of multiple quantities (e.g., female fitness under varying male exposure), and we demonstrate the increased insight that is gained by manipulating male exposure to quantify these quantities.